Impairment of Hepcidin Upregulation by Lipopolysaccharide in the Interleukin-6 Knockout Mouse Brain - Zhang, Fa-Li; Hou, Hui-Min; Yin, Zhi-Nan; Chang, Lan; Li, Fe-Mi; Chen, Y.-J.; Ke, Ya; Qian, Zhong-Ming (Frontiers in Molecular Neuroscience, 2017)
To find out whether the Interleukin-6 (IL-6) / signal transducer and activator of transcription 3 (STAT3) signaling pathway is involved in the expression of hepcidin in the mouse brain in vivo, we investigated the phosphorylation of STAT3, as well as the expression of hepcidin mRNA, ferroportin 1 (Fpn1) and ferritin light chain (Ft-L) proteins in the cortex and hippocampus of LPS-treated wild type (IL-6+/+) and IL-6 knockout (IL-6-/-) mice. We demonstrated that IL-6 knockout could significantly reduce the response of hepcidin mRNA, phospho-STAT3, Fpn1 and Ft-L protein expression to LPS treatment, in both the cortex and hippocampus of mice. Also, Stattic, an inhibitor of STAT3, significantly reduced the expression of phospho-STAT3 and hepcidin mRNA in the cortex and hippocampus of the LPS-treated wild type mice. These findings provide in vivo evidence for the involvement of the IL-6/STAT3 signaling pathway in the expression of hepcidin.